Empowering Urban Educational Leadership: Exploring the Nexus of Educational Leadership, Teacher Compensation, and Socioeconomic Equity in an Urban School District in a Mid-Atlantic State in the United States of America - Anucha, Hyacinth (Advances in Social Sciences Research Journal, 2024)
This study examined teacher leadership, the intricate interplay of culture, education, and the college board race gaps in SAT scores, and their collective impact on academic performance within the Baltimore City Public Schools. The study specifically explored the correlation between teacher salaries and academic achievement while considering persistent factors such as poverty, which consistently hindered academic success for predominantly Black and Brown students, as many seasoned teachers are exiting and too few are joining the profession. Ineffective leadership and inadequate teacher compensation, compounded by the challenges of poverty, were identified as major contributors to below-average academic performance in the urban public school system. Emphasizing teacher salaries, the research highlighted the linear relationship between salary increases and the growing issue of poverty among educators when adjusted for inflation. The meta-analysis conducted underscored the pivotal role played by effective leadership and quality education in enhancing student achievement and fostering socioeconomic growth. The study contended that educational and teacher leadership at the intersection of culture are imperative for adapting to 21st-century economic, technological, and societal transformations. The findings underscored the importance of addressing socioeconomic disparities among educational leaders to improve academic outcomes in urban public schools. Achieving fair compensation, resource accessibility, and fostering professional growth are crucial for attracting and retaining excellent educators, thereby creating an ideal learning environment for all students. The research provided a comprehensive framework for evidence-based parameter estimations in computational modeling, providing informed strategies to address challenges in urban public-school systems.